The Role of Mass Media Amid the Covid-19 Pandemic The Role Of Mass Media In The Midst Of The Covid-19 Pandemic - Fahri Ihsanudin; Tiara Mediana; Pani Audria (Trigin Publisher, 2020)
Mass media is a means of disseminating information to the public, mass media is defined as a medium of communication and information that disseminates information en masse and can be accessed by the public at large, in terms of meaning, mass media is a tool or means to disseminate news content, opinions, comments, entertainment, and so on. The effect of communication on the role of mass media in the midst of the COVID-19 pandemic was identified in the six questions contained in the questionnaire. This study focuses more on the Communication Effects felt by the community, especially on people who have seen health service advertisements about the 5M health protocol. In the health service advertisement, the 5M protocol reminds us that to break the Covid-19 chain, we must wear masks, wash our hands, keep our distance, limiting mobility and avoiding crowds. The results of the study show that the influence of mass media with the presence of 5M health service advertisements affects the behavior and daily activities of the community.